Unified Approach of Unmanned Surface Vehicle Navigation in Presence of Waves. (19th December 2011) - Gal, Oren
Abstract : Most of the present work for unmanned surface vehicle (USV) navigation does not take into account environmental disturbances such as ocean waves, winds, and currents. In some scenarios, waves should be treated as special case of dynamic obstacle and can be critical to USV's safety. For the first time, this paper presents unique concept facing this challenge by combining ocean waves' formulation with the probabilistic velocity obstacle (PVO) method for autonomous navigation. A simple navigation algorithm is presented in order to apply the method of USV's navigation in presence of waves. A planner simulation dealing with waves and obstacles avoidance is introduced.